Psychological Aspects of Activating the Approbation Process of Creative Mathematical Thinking - Lidiia Moiseienko; Liubov Shehda (Проблеми сучасної психології)
The purpose of the article is to find out the potential influence of cause and effect questions on the approbation process of creative mathematical thinking in order to activate it.